Heterogeneous intermediaries in the transmission of central bank corporate bond purchases - Fédéric Holm-Hadulla; Matteo Leombroni (European Central Bank (ECB), 2025)
This paper studies the role of financial intermediaries in the transmission of central bank corporate bond purchases to bond yields. Contrary to standard expectations, we find that mutual funds-typically viewed as price-elastic investors-amplify, rather than dampen, the effects of these interventions on bond spreads. Following the ECB's corporate bond purchase announcements in 2016 and 2020, bonds predominantly held by mutual funds experienced significantly larger and more persistent declines in spreads compared to those held by price-inelastic investors such as insurance companies, even after controlling for a broad set of bond characteristics. Drawing on additional empirical evidence and an equilibrium asset pricing model, we show that the state-contingent nature of the policy reduces perceived market risk for procyclical investors like mutual funds, thereby boosting demand and compressing risk premia.
Keywords: E52; E58; G11; G23; 330; Corporate bonds; non-bank financial institutions; central bank asset purchases